2022
DOI: 10.1039/d2dt02908a
|View full text |Cite
|
Sign up to set email alerts
|

High-valence chromium accelerated interface electron transfer for water oxidation

Abstract: High-valence Cr ions at the interface between an alloy core and a reconstruction layer shell served as powerful electron acceptors, accelerating the electron transfer by means of the exchange effect of the Ni–O–Cr configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…As a cocatalyst, Cr synergistically improves the electrocatalytic activity . It is worth noting that relevant studies have shown that the presence of high-valence Cr enables a stronger interaction with the carbon matrix, reducing the adsorption free energy of OER intermediates at the active site and thus enhancing the OER activity. However, high-valence Cr-based catalysts are usually difficult to obtain due to the requirement of high-temperature reactions and the use of oxidants. Therefore, we designed controlled pyrolysis to prepare chromium-oxide-based nanomaterials with a high oxidation state, expecting superior OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…As a cocatalyst, Cr synergistically improves the electrocatalytic activity . It is worth noting that relevant studies have shown that the presence of high-valence Cr enables a stronger interaction with the carbon matrix, reducing the adsorption free energy of OER intermediates at the active site and thus enhancing the OER activity. However, high-valence Cr-based catalysts are usually difficult to obtain due to the requirement of high-temperature reactions and the use of oxidants. Therefore, we designed controlled pyrolysis to prepare chromium-oxide-based nanomaterials with a high oxidation state, expecting superior OER performance.…”
Section: Introductionmentioning
confidence: 99%